Glossário bilíngue online na área de tecnologia da informação - Holanda, Fabiola Silveira Jorge (2023)
The main objective of this study is to list specialized expressions and terms in English, and their equivalents in Portuguese, used in the area of information technology (IT). To adequately fulfill this aim, we consider knowledge regarding the linguistic-grammatical patterns manifested in authentic texts and in the real use of the language explained by Corpus Linguistics (Berber Sardinha, 2000, 2004; Sinclair, 1991; Tognini-Bonelli, 2001). In conjunction with this methodological basis, we evoke the constituent principles of the Communicative Theory of Terminology proposed by Cabré (1999), in order to compare, in a consistent way, the particularities of Terminology. In fact, our interest in offering an understanding that is not Only advanced, but also articulated about the assumptions of terminological epistemology is such that we will propose, based on the resources of the Theory of Multimodality developed by Kress and Van Leewen (2006; 2011), the development of a bilingual, multimodal electronic glossary that is attractive to the user. Classified as qualitative, the study is exploratory-descriptive in nature and it was conducted at three different moments: (1) application of questionnaires to students from different courses in the IT area on the campuses of the Instituto Federal de Educação, Ciência e Tecnologia do Ceará (IFCE ) and to the members of the Apple Developer Academy project, at IFCE – Campus Fortaleza; (2) carrying out extensive research in the chosen English-language corpus, Sage Journal, in order to identify specialized terms and expressions; (3) use of the WordSmith Tools 8.0 program (Scott, 2021) and its Concord and Wordlist tools to analyze the frequency and keyness of terms, in addition to the concordancers that accompany them. This resulted in the English-Portuguese bilingual electronic glossary, designed in the form of an application, capable of being used on multiplatform systems, with paradigms that will benefit consultants, mainly in terms of communicative written competence in English, in addition to having elaborate illustrative images, exclusively to provide a better understanding of the terms.